2011
DOI: 10.1002/jcp.22537
|View full text |Cite
|
Sign up to set email alerts
|

Activation and induction of cytosolic phospholipase A2 by TNF‐α mediated through Nox2, MAPKs, NF‐κB, and p300 in human tracheal smooth muscle cells

Abstract: Cytosolic phospholipase A(2) (cPLA(2)) plays a pivotal role in mediating agonist-induced arachidonic acid (AA) release for prostaglandin (PG) synthesis during inflammation triggered by tumor necrosis factor-α (TNF-α). However, the mechanisms underlying TNF-α-induced cPLA(2) expression and PGE(2) synthesis in human tracheal smooth muscle cells (HTSMCs) remain unknown. Here, we report that TNF-α-induced cPLA(2) protein and mRNA expression, PGE(2) production, and phosphorylation of p42/p44 MAPK, p38 MAPK, and JNK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 53 publications
3
46
1
Order By: Relevance
“…We and others have clearly demonstrated that the human cPLA 2 ␣ promoter (in our studies, extending to approximately Ϫ 6.8 kb) is not responsive to cytokine activation (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). This discrepancy may result from these investigators' use of diseased synovial fi broblasts in conjunction with IL-1 ␤ concentrations 15 times (30 ng/ml) higher than our dosage and well beyond physiologically relevant levels.…”
Section: Generation Of Promoter and Enhancer Constructs In Human Growcontrasting
confidence: 61%
See 1 more Smart Citation
“…We and others have clearly demonstrated that the human cPLA 2 ␣ promoter (in our studies, extending to approximately Ϫ 6.8 kb) is not responsive to cytokine activation (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). This discrepancy may result from these investigators' use of diseased synovial fi broblasts in conjunction with IL-1 ␤ concentrations 15 times (30 ng/ml) higher than our dosage and well beyond physiologically relevant levels.…”
Section: Generation Of Promoter and Enhancer Constructs In Human Growcontrasting
confidence: 61%
“…cPLA 2 ␣ expression and activity through the proximal promoter, including nuclear factor (NF)-B ( 22,23 ), Krüppel-like factor (KLF) ( 24,25 ), hypoxia-inducible factor (HIF-1) ( 26 ), and specifi city protein 1 (Sp1) ( 27 ). A 48 bp CA dinucleotide repeat at approximately Ϫ 200 bp has been shown to confer a negative regulatory effect on cPLA 2 ␣ basal promoter activity ( 16,28 ).…”
Section: Generation Of Promoter and Enhancer Constructs In Human Growmentioning
confidence: 99%
“…These analyses also confirmed the identification of several proteins known to be modulated by TNF-␣, such as cPLA 2 and TRAP1. Previous reports have described the activation of cPLA 2 upon TNF-␣ activation of macrophages (48,49). This protein is activated by calcium and comprises both lysophospholipase and transacylase activities.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is one of the key factors of atherosclerosis detected in VSMCs, macrophages, and endothelial cells from human atherosclerotic lesions (Brand et al, 1996). Even though inflammatory cytokines such as TNF-α (Lee et al, 2011) or advanced glycation endproducts (Yoon et al, 2009) promoted the progression of atherosclerosis through activation of NF-κB pathway, that is not adequate evidences which explain about the direct effect of hyperglycemia itself in diabetic vasculopathy. Therefore, in this study, we observed that activation of NF-κB was stimulated by high concentrations of glucose as evidenced by translocation of the p65 subunit, increased luciferase activity, and degradation of IκB-α.…”
Section: Discussionmentioning
confidence: 99%